2020
DOI: 10.1213/ane.0000000000005017
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Interaction Between Butorphanol and κ-Opioid Receptor

Abstract: BACKGROUND: The misuse of opioids stems, in part, from inadequate knowledge of molecular interactions between opioids and opioid receptors. It is still unclear why some opioids are far more addictive than others. The κ-opioid receptor (KOR) plays a critical role in modulating pain, addiction, and many other physiological and pathological processes. Butorphanol, an opioid analgesic, is a less addictive opioid with unique pharmacological profiles. In this study, we investigated the interaction betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 29 publications
0
25
0
1
Order By: Relevance
“…Butorphanol is known to act as a partial agonist of KOR in the G-protein activation signaling pathway (24). The results of western blot analysis revealed that LPS stimulation downregulated the expression levels of KOR in H9C2 cells, whereas the expression levels of KOR were upregulated following butorphanol treatment (Fig.…”
Section: Butorphanol Upregulates the Expression Of Kor In Lps-induced H9c2 Cellsmentioning
confidence: 90%
“…Butorphanol is known to act as a partial agonist of KOR in the G-protein activation signaling pathway (24). The results of western blot analysis revealed that LPS stimulation downregulated the expression levels of KOR in H9C2 cells, whereas the expression levels of KOR were upregulated following butorphanol treatment (Fig.…”
Section: Butorphanol Upregulates the Expression Of Kor In Lps-induced H9c2 Cellsmentioning
confidence: 90%
“…Butorphanol is a partial μ-opioid receptor (MOR) agonist that also exhibits 20fold higher affinity for KOR. This synthetic opioid demonstrates higher potency and lower dependence when compared with morphine (54). Butorphanol is available as a narcotic analgesic in parenteral and transnasal formulations, although tolerability may be limited by central nervous effects including somnolence, nausea, and vomiting (55).…”
Section: κ-Opioid Agonistsmentioning
confidence: 99%
“…Clinical drugs targeting KOR, such as oxycodone ( 178 ) and butorphanol ( 179 ), are KOR/MOR mixed agonists. Similar to morphine, oxycodone inhibits proliferation and migration of human lung adenocarcinoma cells and induces apoptosis ( 180 ).…”
Section: Effects Of Opioids On Tumorsmentioning
confidence: 99%